Malignant transformation of uterine leiomyoma to myxoid leiomyosarcoma after morcellation associated with ALK rearrangement and loss of 14q - Holzmann, Carsten; Saager, Christian; Mechtersheimer, Gunhild (OncoTarget, 2018)
Oncotarget | https://doi.org/10.18632/oncotarget.25137 Carsten Holzmann, Christian Saager, Gunhild Mechtersheimer, Dirk Koczan, Burkhard M. Helmke, Jörn Bullerdiek